(untitled) (Bangladesh Journal of Medical Science, 2015)
A female child of age five attended our institution in Jan 2006 with repeated upper respiratory infection. Plain skiagram and CT examinations confirmed the case to be a Scimitar syndrome. DOI: http://dx.doi.org/10.3329/bjms.v14i1.21576 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.103-105